2017
DOI: 10.2196/publichealth.6872
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient Narratives in Disease Blogs on the Internet: An Exploratory Study of Social Pharmacovigilance

Abstract: BackgroundAlthough several reports have suggested that patient-generated data from Internet sources could be used to improve drug safety and pharmacovigilance, few studies have identified such data sources in Japan. We introduce a unique Japanese data source: tōbyōki, which translates literally as “an account of a struggle with disease.”ObjectiveThe objective of this study was to evaluate the basic characteristics of the TOBYO database, a collection of tōbyōki blogs on the Internet, and discuss potential appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
(31 reference statements)
0
18
0
1
Order By: Relevance
“…The results emphasized that this unique population of patients and caregivers used Internet resources in a variety of ways. As with other individuals who have unique healthcare needs, 14,15 transgender youth and caregivers search for knowledge and information about transgender health, gender terms, and gender-affirming care. Online searches are used both to explore terminology and identify others who may be undergoing a similar experience.…”
Section: Discussionmentioning
confidence: 99%
“…The results emphasized that this unique population of patients and caregivers used Internet resources in a variety of ways. As with other individuals who have unique healthcare needs, 14,15 transgender youth and caregivers search for knowledge and information about transgender health, gender terms, and gender-affirming care. Online searches are used both to explore terminology and identify others who may be undergoing a similar experience.…”
Section: Discussionmentioning
confidence: 99%
“…These positive and negative aspects of ITC, in turn, influence what practitioners and the broader public understand about MCM safety and efficacy, thus presenting new challenges and opportunities for crisis and risk communicators. Medication users, for example, are increasingly sharing personal knowledge and experience of drug benefits and risks via online disease support networks, patient and drug forums, and microblogging (Matsuda, 2017;Sloane et al, 2015). Through social media, these individuals can find both practical information and a sense of community, while drug safety professionals have a new, rich data source with which to mine for potential evidence of adverse events, supplementing uneven healthcare provider reports (Edwards & Lindquist, 2011;Inch et al, 2012).…”
Section: Social Media Challenges/opportunities For Health and MCM Commentioning
confidence: 99%
“…User comments in health-related social networks contain extractable information relevant to pharmacovigilance. Research efforts focused on both general health discussion forums [65][66][67][68][69] and disease-specific discussion forums [46,70,71] have demonstrated that it is possible to extract complex medical concepts, with relatively high performance, from informal, user-generated content.…”
Section: Specialised Healthcare Social Network and Forumsmentioning
confidence: 99%